Analysis of Prognostic Factors Relating to Postoperative Survival in Spinal Metastases - Yang, Soon Bum; Cho, Wonik; Chang, Ung-Kyu (Journal of Korean Neurosurgical Society, 2012)
To analyze the prognostic factors thought to be related with survival time after a spinal metastasis operation. We retrospectively analyzed 217 patients who underwent spinal metastasis operations in our hospital from 2001 to 2009. Hematological malignancies, such as multiple myeloma and lymphoma, were excluded. The factors thought to be related with postoperative survival time were gender, age (below 55, above 56), primary tumor growth rate (slow, moderate, rapid group), spinal location (cervical, thoracic, and lumbo-sacral spine), the timing of radiation therapy (preoperative, postoperative, no radiation), operation type (decompressive laminectomy with or without posterior fixation, corpectomy with anterior fusion, corpectomy with posterior fixation), preoperative systemic condition (below 5 points, above 6 points classified by Tomita scoring), pre- and postoperative ambulatory function (ambulatory, non-ambulatory), number of spinal metastases (single, multiple), time to spinal metastasis from the primary cancer diagnosis (below 21 months, above 22 months), and postoperative complication. The study cohort mean age at the time of surgery was 55.5 years. The median survival time after spinal operation and spinal metastasis diagnosis were 6.0 and 9.0 months. In univariate analysis, factors such as gender, primary tumor growth rate, preoperative systemic condition, and preoperative and postoperative ambulatory status were shown to be related to postoperative survival. In multivariate analysis, statistically significant factors were preoperative systemic condition (p=0.048) and postoperative ambulatory status (p<0.001). The other factors had no statistical significance. The factors predictive for postoperative survival time should be considered in the surgery of spinal metastasis patients.